Health professional's implicit bias of adult patients with low socioeconomic status (SES) and its effects on clinical decision-making: a scoping review protocol. Issue 12 (12th December 2022) - Job, Claire; Adenipekun, Bami; Cleves, Anne; Samuriwo, Ray
Abstract : Introduction: Despite efforts to improve population health and reduce health inequalities, higher morbidity and mortality rates for people with lower socioeconomic status (SES) persist. People with lower SES are said to receive worse care and have worse outcomes compared with those with higher SES, in part due to bias and prejudice. Implicit biases adversely affect professional patient relationships and influence healthcare-related decision-making. A better understanding of the relationship between SES and healthcare-related decision-making is therefore essential to address socioeconomic inequalities in health. Aim: To scope the reported impact of health professionals bias about SES on clinical decision-making and its effect on the care of adults with lower SES in wider literature. Methods: This scoping review will use Joanna Briggs Institute methods and will report its findings in line with Preferred Items for Systematic Reviews and Meta-Analyses for Protocols and Scoping Reviews guidelines. Data analysis, interpretation and reporting will be underpinned by the PAGER ( P atterns, A dvances, G aps, E vidence for Practice and R esearch recommendations) framework and input from a patient and public interest representative. A systematic search for literature will be conducted on various, pertinent databases to identify relevant literature such as peer-reviewed articles, editorials, discussion papers and empirical research papers. Additionally, other sources of relevant literature such as policies, guidelines, reports and conference abstracts, identified through key website searches will be considered for inclusion. Ethics and dissemination: Ethical approval is not required for this scoping review. The results will be disseminated through an open access peer-reviewed international journal, conference presentations and a plain language summary that will be shared with the public and other relevant stakeholders.